2014
DOI: 10.1007/978-3-319-07320-0_4
|View full text |Cite
|
Sign up to set email alerts
|

The DING Family of Phosphate Binding Proteins in Inflammatory Diseases

Abstract: Human paraoxonase 1 (hPON-1) is a protein that has been studied in relation to its antioxidant and anti-atherosclerotic properties. Despite extensive studies, the molecular mechanisms responsible for its functional properties remain unclear. During the last decade, a new partner of hPON-1 has been identified. Hidden for a long time because of a similar molecular weight with hPON-1, this protein, termed human phosphate-binding protein (HPBP), may contribute to the biological functions of hPON-1. Belonging to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…This is consistent with the sub-angstrom X-ray structure analysis. 18,19,23 In the sub-angstrom X-ray crystallography studies of PfluDING, only one proton on oxygen atoms of the phosphate was observed at pH 4.5 and 8.5. PfluDING and E. coli PBP are topologically similar with a structural rmsd value of 1.34 Å over 228 Cα carbons and 0.23 Å over all heavy atoms in the binding pocket.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is consistent with the sub-angstrom X-ray structure analysis. 18,19,23 In the sub-angstrom X-ray crystallography studies of PfluDING, only one proton on oxygen atoms of the phosphate was observed at pH 4.5 and 8.5. PfluDING and E. coli PBP are topologically similar with a structural rmsd value of 1.34 Å over 228 Cα carbons and 0.23 Å over all heavy atoms in the binding pocket.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This again agrees with sub-angstrom crystallography studies. 18,19,23 It should be noted that constant-pH MD is an alternative way to determine the protonation state of titratable groups. 43,44 In addition, the binding free energies of 1H phosphate are similar for the wild-type and the mutant protein, consistent with experimental measurements.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations